The Mutant Problem: X-Men, Confirmation Bias, and the Methodology of Comics and Identity - Martin Lund (European Journal of American Studies)
This article suggests that scholarship on comics and identity is vulnerable to strong confirmation bias. Engaging with a few common assumptions presented in writing on X-Men comics(1963–1970, 1975–1991) and identity, it offers alternative interpretations on the series’ engagement with the Cold War, civil rights, individual authenticity, persecution, and the Holocaust. Based on these discussions, the article then offers a few methodological suggestions that might help reduce bias in future studies of comics and identity.